A comparative study of five plateletpheresis machines in a tertiary care center of India: AmiCORE vs COM.TEC vs Haemonetics MCS+ vs Spectra Optia vs Trima Accel. Issue 1 (7th September 2020) - Arcot, Priyadarsini Jayachandran; Kumar, Karan; Coshic, Poonam; Andriyas, Vijay; Mehta, Vikas
Abstract: Background: Single donor apheresis platelets are superior in quality, but their usage is limited in a developing country due to cost and time constraints. Hence the product obtained must exceed in terms of yield, donor safety and technical convenience. Previous literature available on cell separators is on older versions. Aims: Prospective comparison of 5 latest cell separators (AmiCORE, COM.TEC, Haemonetics MCS+, SpectraOptia and TrimaAccel) for product yield, performance variables and donor adverse effects. Material & Methods: From October 2019 ‐ March 2020, 1108 donors were randomly allotted to a cell separator. Post‐donation sample was taken from the donor 15‐20 minutes after procedure completion. The platelet yield from the product collected was measured twice (day 0 and day 1). Donor demography, pre‐and post‐procedural donor peripheral blood values, performance and product variables were statistically analyzed. Results: AmiCORE had an optimal collection efficacy (44.6%) and collection rate (0.037 x 1011/minute). Haemonetics MCS+ had a better collection efficacy (48.4%) and rate (0.038 x 1011/minute). Spectra Optia achieved least procedural time (59.5 minutes), donor adverse effects (6.3%); highest collection efficacy (52.8%) and rate (0.056 x 1011/minute). Trima Accel achieved highest collection rate (0.056 x 1011/minute) and the least product volume (228 ml). Conclusion: Highest collection efficacy was achieved by Trima Accel, highest collection rate by Trima Accel and Spectra Optia, lowest donor adverse effects by Spectra Optia and least number of procedural troubleshooting by COM.TEC. Apart from this, fiscal factors and service availability also need to be considered before choosing a cell separator.